Hyperkalemia on ECG - Bryson Hicks (Journal of Education and Teaching in Emergency Medicine, 2016)
History of present illness: A 34-year-old diabetic female presented to the emergency department with chest pain status-post AICD firing. She described the pain as a “12 out of 10” which woke her from sleep at 0200, one hour prior to arrival. Vitals were unremarkable. She had no known history of renal failure. Due to frequent ED visits for chronic pain, patient had difficult vascular access and nursing was initially unable to obtain IV access. An abnormal rhythm was noted on the cardiac monitor, and ECG was ordered.